LUNTURNYA KEARIFAN LOKAL PERMAINAN TRADISIONAL PADA SISWA SMP NEGERI 1 PURWODADI - Annisa, Azizah Nur; Sari, Livi Fatma; Bachri, Muchammad Syamsul; Fauroni, Muhammad Rizqon; Setiani, Rohmah (Universitas Hasanuddin, 2019)
The traditional game is the local wisdom of every region in Indonesia. Indonesia has a diversity of classic games with different characters in each area. The positive thing that is found in traditional games is that it can embed the noble values of the nation such as, the virtuous, spirit of cooperation/togetherness, honesty, and obedience to the rules. The exact amount of traditional games must continue to be preserved. The biggest challenge in defence is the development of difficult-to-be-dammed technology. Based on the background, this research wants to apply various traditional games in SMP Negeri 1 Purwodadi by reviewing the cause of the start-up, traditional games, students ' responses when traditionally used games, and the benefits that Acquired traditional games. Research method with a qualitative approach. Data collection techniques with observations and interviews. The results of this research are the first, and there are various causes of the traditional game if it is reviewed from the socio-cultural, environmental, legal, and historical aspects. Secondly, the enthusiastic response of students depicting that traditional games can also provide the satisfaction of playing during sophisticated technology. Thirdly, traditional game benefits can instil the sublime value of the nation.